Statistical Evaluation of Grass Yield from Sabai [Eulaliopsis binata (Retz.) Rubb.] on Bouldery Riverbed of Doon Valley - Gupta, R. K.; Agarwal, M. C.; Kumar, Nirmal (Indian Forester, 1995)
Eulaliopsis binata (Retz.) Rubb. a potential industrial grass is recommended for soil formation, preventing erosion and facilitating utilization of eroded dry bouldery in North-West India. The potential of the standing grass was computed through various additive and multiplicative regression models between green or air-dry yield and various growth attributes (plant height, clump diameter and number of tillers) by taking one, two or all the three attributes together. From this study, it was concluded that the prediction of green or air-dry yield can be made precisely through multiplicative model having two growth attributes (viz. plant height and number of tillers) particularly on bouldery riverbed of Doon Valley.